Establishing the relative Contributions of exposure to maternal obesity during gestation and lactation on offspring metabolic health - Robinson, Grace (2018)
Introduction: Exposure to maternal obesity during early development can have profound consequences for health and programme for obesity and type-2 diabetes. However, the mechanisms of programming during gestation and lactation are poorly understood. Aim: To assess the relative contributions of exposure to maternal obesity, induced by a cafeteria diet, during gestation and lactation on rat offspring growth, behaviour, metabolic and cardiovascular health. Methods: A cross-fostering study was piloted and then implemented to assess the relative contributions of maternal obesity during pregnancy and lactation. Female Wistar rats were fed either a control (C) or cafeteria diet (O) for two weeks before mating in the pilot study and eight weeks in the second experiment, throughout pregnancy and lactation. Offspring were cross-fostered at birth to a dam on the same or alternate diet to before birth and weaned on a chow diet. The pilot study also compared offspring cross-fostered (CF) against those that were not (NCF). Endpoints measured in offspring comprised weight and body composition, blood pressure, circulating and hepatic lipids, glucose tolerance, locomotor behaviour and gene expression. Results: The pilot study identified no difference between CF and NCF groups in offspring body composition, blood pressure, glucose tolerance, or plasma TAG and cholesterol concentrations at eight weeks of age. Therefore, cross-fostering was an effective method for a larger scale experiment. Feeding female dams a highly varied cafeteria diet resulted in greater weight and 3.4 times greater adiposity than animals fed a control chow diet throughout pregnancy and lactation (P<0.05). Exposure to maternal obesity during pregnancy was associated with lower birth weight in offspring, reduced locomotor behaviour in female offspring at eight weeks of age, and elevated hepatic omega 3 fatty acid composition in male offspring at twelve weeks of age. Exposure to maternal obesity in lactation was associated with reduced locomotor behaviour in male offspring at twelve weeks of age. It was also associated with greater adiposity. Compared to control offspring, male offspring had 40% greater perirenal adiposity at two weeks of age (P=0.043) and female offspring had 26% greater gonadal adiposity at twelve weeks of age (P=0.030). Fasting blood glucose concentrations were 8% greater in offspring exposed to maternal obesity during lactation (P=0.031) and male offspring demonstrated slower glucose clearance during a two-hour intraperitoneal glucose tolerance test, despite no differences in circulating insulin between groups. This indicated insulin resistance, which was further confirmed by reduced adipose tissue and hepatic mRNA expression of genes which code for the regulatory and catalytic subunits of PI3K, in the insulin signalling cascade. However, male offspring exposed to maternal obesity during gestation demonstrated up-regulation of insulin signalling genes in skeletal muscle and perirenal adipose tissue. An insulin resistance PCR array confirmed an mRNA expression profile favouring insulin sensitivity in offspring exposed to maternal obesity during gestation (key genes included ALOX5, APOE, CASP1, CCL12, STAT3, TNF P<0.001) and resistance in offspring exposed to maternal obesity during lactation (CXCR4, OLR1, CCR5, TNF, P<0.05). Conclusions: Cross-fostering successfully teased apart the relative contributions of exposure to maternal obesity before birth and during lactation. Maternal obesity during lactation has a greater influence in programming for insulin resistance and adiposity than maternal obesity in pregnancy.